Decoding Women’s Struggle in Inshallah Walad: A Peircean Semiotic Analysis of Amjad Al Rasheed’s Film - Nurmilatussa'adah Nurmilatussa'adah; Asep Supianudin; Muhammad Nurhasan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study examines the representation of women’s struggle in Inshallah Walad, directed by Amjad Al Rasheed, which portrays various forms of injustice experienced by women within a patriarchal social system. The study addresses the issue of how cinematic signs reflect women’s resistance and survival amid social, legal, and emotional oppression. It aims to analyze the forms and meanings of women’s struggle using the semiotic framework of Charles Sanders Peirce. Employing a qualitative library research method, data were collected from film dialogues, visual scenes, and relevant scholarly sources, then analyzed through Peirce’s triadic model of sign interpretation. The findings reveal five major representations of women’s struggle: resistance to patriarchal domination, efforts to defend rights and identity, strategic social negotiation, the preservation of dignity and personal freedom, and emotional resilience. This study contributes to the enrichment of semiotic and gender studies, particularly in understanding women’s representation in contemporary Middle Eastern cinema.